Exploitation of northern peatlands and biodiversity maintenance: a conflict between economy and ecology. Issue 10 (1st December 2003) - Chapman, Steve; Buttler, Alexandre; Francez, André-Jean; Laggoun-Défarge, Fatima; Vasander, Harri; Schloter, Michael; Combe, Jean; Grosvernier, Philippe; Harms, Hauke; Epron, Daniel; Gilbert, Daniel; Mitchell, Edward
Abstract : Peatlands are ecosystems of exceptional conservation value because of their beauty, biodiversity, importance in global geochemical cycles, and the paleoenvironmental records they preserve. Commercial extraction and drainage for forestry or agriculture have caused the destruction of many peatlands, especially in or close to urban areas of the northern temperate zone. Are these commercial and environmental interests irreconcilable? A close analysis suggests that limited peat extraction may actually increase biodiversity in some cases, and may be sustainable over the long term. As we learn more about how peatlands spontaneously regenerate following disturbance, and what conditions govern the re‐establishment of a diverse community and the ability to sequester carbon, we increase our chances of being able to restore damaged peatlands. Preserving the chronological records hidden in the peat profile, the natural heritage value of peatlands, and the bulk of sequestered carbon, however, will remain incompatible with any form of exploitation.